(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The Bible presents an undeniable message that God is interested in the prosperity and well-doing of those who believe in him, including Christians. However, instead of balancing faith and work, able young Ghanaian Christians pray almost all hours, staying in churches, being idle. Moreover, women leave their “capital-invested” shops for prayer camps during working days and hours, whereas some preachers craftily exploit ignorant members in the name of “special programmes and seed-sowing.” Sadly, some Christians in Ghana are made to believe that positive confessions and faith are enough to make one successfully prosperous. Meanwhile, long before the emergence of “prosperity gospel,” Akan-Ghanaians knew that “Sika yε mogya,” literally meaning “Money is blood.” This study is a literature-based research and examines scholarly discourses on “prosperity gospel” – globally, in Africa, in contemporary Ghanaian Christianity; making reference to the Akan-Ghanaian dynamic notions in the eyes of discipleship and Christian conduct amid suffering, with critical reflections and dialogues from Dietrich Bonhoeffer’s “The cost of discipleship, 1979 edition” and John R.W. Stott’s “Men with a Message” in the light of Mark 8:34-38 and the Petrine letters. Findings reveal that our prosperity is cost-involved. It requires both faith in God and our intentional determination, dedication, discipline and sacrifice toward work and shunning every form of idleness and religious laziness. One should work to reap physical and material possessions inasmuch as they have faith in God. Contextually, regarding prosperity, Bonhoeffer emphasizes that there is no free-zone, but rather the disciple of Jesus Christ should bear the costs of obedience, followership and suffering. John Stott agrees with Peter and therefore admonishes Christians that, amid their obedience and suffering (toward prosperity), they should: follow Jesus’ example, know that Jesus suffered to bring them to God, love one another as God’s chosen people, have a living hope of their glorification and thus should continue to show goodness and live holy in expectation. Moreover, Peter admonishes Christians to respect human authorities and not to disregard them as enemies. Thus, prosperity gospel in contemporary Ghanaian Christianity requires Christians to build a balance between faith that saves and the work that yields the income. The absence of the latter encourages socio-religious laziness, fruitlessness and poverty. Significantly, this paper is relevant for academic literature on poverty-reduction theologies, socio-economic development as well as the financial liberation of poor and ignorant Christians through building balance between faith and work.